Quand les « premiers de cordée » coupent la corde derrière eux… et créent leur « régime spécial » - Camille Noûs (La Nouvelle Revue du Travail)
The current French government has evoked the ideals of «social justice» to restructure the national pension system. In reality, however, the goal is financialisation and actually immiseration, based notably on more highly paid employees being allowed to pay less into the general system while benefiting themselves from a new «special regime». In truth, the purpose of France’s new «universal» system is to give a small fraction of affluent wage-earners permission to organise their own secession.